Attempting to explore chiropractors and their clinical choices: an examination of a failed study - Stanley I. Innes; Charlotte Leboeuf-Yde; Bruce F. Walker (Chiropractic & Manual Therapies, 2019)
Abstract Background Recent studies have shown that psychological factors, attitudes and beliefs impact on the quality of chiropractic student clinical decisions. This association has not been studied among qualified chiropractors. Our objective was to investigate if personality, psychological factors and/or unorthodox beliefs among chiropractors are related to choices of management in specific clinical scenarios. Method In February 2018, a subsample of chiropractors (N = 700) from a practitioner-based research network in Australia known as ACORN (N = 1680), were invited to respond to an on-line anonymous questionnaire. Questions included items relating to management of specific clinical scenarios, intolerance of uncertainty (IU) and the ‘Big-5’ personality score, adoption of a prescriptive technique system, self-rating of chiropractic abilities, and the level of importance of subluxation and chiropractic philosophy in the delivery of care. Descriptive analysis was to be reported and associations examined between i) personality and psychology factors, unorthodox beliefs and ii) scores obtained for management of specific clinical scenarios, numbers of interdisciplinary referrals, and guideline-based X-ray use. Results The number of respondents was 141 (20%) and 33 of their responses were largely incomplete resulting in a final response rate of 108 (15.4%). In addition, some questions were left unanswered. These related mainly to IU and Big-5 personality measurements. Some sample characteristics (age, number of patients per week, hours worked per week) were similar to the larger ACORN project sample. However, the low response rate indicated that the final study sample was unlikely to be truly representative of the study population and the low number of participants made association testing unsuitable. Conclusion and recommendations The low response rate and small study sample in this study made any substantive analysis inappropriate. For these reasons, the study was not concluded. However, the potential reasons for the low response from this large database of volunteer research participants are of interest and need to be investigated. Clearly, it is necessary to engage this population better to explore sensitive issues such as personality inventories and different practice profiles in the interest of effective health care delivery and patient safety.